Analisis Nilai Tambah Pengolahan Kopi Arabika Di Kelompok Tani Sejahtera Kabupaten Situbondo - Puryantoro, Puryantoro (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2021)
Coffee is one of the mainstay commodities in Situbondo Regency. Kayumas Village, Arjasa District is the best coffee producer that has ever received a national award. The Arabica coffee agro-industry carried out by farmer groups provides promising added value to the business world. This study aims to analyze the added value in the agro-industry of fullwash coffee and natural arabica in the Prosperous Farmer Group in Kayumas Village, Arjasa District, Situbondo Regency. Data collected in March 2020 through primary and secondary data were analyzed using the Hayami method. The results showed that the added value of processing Arabica coffee into full-wash and natural Arabica brewed coffee gave the same added value, namely Rp. 50,600 or 40.48% with different benefits. Fullawash got a profit of Rp. 47,600 / kg and naturally get a profit of Rp. 46,850 / kg.